Phylogenetic studies on the genus Candolleomyces (Psathyrellaceae, Basidiomycota) occurring in the bed of the Indus River, Punjab, Pakistan, reveal three new species - Qirui Li; Muhammad Haqnawaz; Abdul Rehman Niazi; Abdul Nasir Khalid (MycoKeys)
During macrofungal surveys in 2019–2024, several specimens belonging to the family Psathyrellaceae were collected from the bed of the Indus River, Punjab, Pakistan. Phylogenetic analyses, based on ITS, LSU, and tef-1α sequences and morpho-anatomical study, confirmed the novelty and placement of three taxa in the genus Candolleomyces. They are described as Candolleomyces crenatus, C. undulatus, and C. virgatus. For distinguishing characters, C. crenatus has crenate cap margins, small basidiospores, and a marginate base of stipe. Candolleomyces undulatus has parabolic to campanulate, wavy margins, light purplish gray with a light brownish gray center of pileus, and an appendiculate, pendant annulus. Candolleomyces virgatus has a parabolic to plane, distinct umbo, a virgate surface of pileus, 1–7 tiers, forking lamellae, and longitudinal striation on the surface of the stipe. Currently, Candolleomyces comprises 60 formally recognized species worldwide. However, with the inclusion of these three species, the total number rises to 63. Detailed descriptions, a phylogenetic estimate, morphological comparisons, and illustrations are provided.